Questioning Human Rights, Looking for Justice: Analyzing the Impact of Supreme Court Circular Letter on Interfaith Marriages in Indonesia - Indrayanti, Kadek Wiwik; Saraswati, Anak Agung Ayu Nanda; Putra, Eka Nugraha (Universitas Negeri Semarang, 2024)
The issuance of Supreme Court Circular Letter (SEMA) Number 2 of 2023 concerning Guidelines for Judges in Adjudicating Cases on Applications for Registration of Marriages between People of Different Religious Beliefs has caused problems regarding interfaith marriages in Indonesia. Both conceptually and in practice, interfaith marriages have long been controversial. Using a human rights approach, this article analyzes SEMA's position in the hierarchy of laws and regulations and the impact of SEMA Number 2 of 2023 on the independence of judges and the practice of interfaith marriages in Indonesia. The results of the analysis indicate that SEMA Number 2 of 2023 is contrary to human rights principles, especially the principles of religious rights, the right to choose a partner and the right to get married. Although the content of SEMA should only be related to technical matters of court processes, SEMA Number 2 of 2023 targets the substance of citizens’ rights; it asks judges to reject requests for the validation of interfaith marriages, even though the issue is clearly regulated by the Law on Population Administration. As a result, the chances of validating interfaith marriages through court decisions are closed. This policy not only limits the independence of judges in deciding such cases but also violates the human rights of citizens.